The Difference of Olfactory Functions in The Workers of The Gas Station by Using Sniffin’ Stickstest in Medan City - Sagala, Irwan Pernandi; Munir, Delfitri; Rambe, Andriana Yunita Murni; Ashar, Taufik (Talenta Publisher, 2018)
Introduction: Chronic exposure of volatile substances can cause the impaired olfactory function. Objectives: In order to identify the difference of olfactory function in the workers of the Gas Station in Medan city. Methods: Analytical research with cross- sectional approach. The research subjects were 80 persons consisting of 40 gas station operators and 40 non-operators who fulfilled the inclusion and exclusion criteria. The applied statistical analysis was Mann Whitney, Fisher's Exact, Chi Square, T independent, Spearman with 95% confidence level. Results: Proportion of the impaired olfactory function in the gas station operator group by 77.5% and non-operator group by 0%. Significant correlation was obtained between age, duration of work with the impaired olfactory function (p = 0,047, p = 0,001). The gas station operators will suffer the impaired olfactory function if they work for  3.89 years. Conclusions: There were differences of olfactory functions in the gas station workers by using Sniffin 'Sticks Test in Medan city.